Experimental investigation of rhombic dodecahedron micro-lattice structures manufactured by Electron Beam Melting. (2019) - Epasto, G.; Palomba, G.; Andrea, D.D'.; Di Bella, S.; Mineo, R.; Guglielmino, E.; Traina, F.
Abstract: The aim of this scientific work is the analysis of rhombic dodecahedron micro-lattice structures under quasi-static and dynamic loading. The effect of unit cell size and strut diameter on mechanical properties was also considered. The specimens were designed by means of Materialise Magics ® software and produced using Ti6Al4V ELI metal powder by Arcam Q10 electron beam melting (EBM) 3D printer, with the scientific collaboration of Mt Ortho Srl. The microstructure effect on the mechanical properties was analysed by optical and electron microscopy and Computed Tomography was used to analyse the morphology of unit cells. The experimental results show that these porous structures are very suitable for building custom-made implants in the field of orthopaedics and reconstructive neurosurgery. Moreover, by means of EBM additive manufacturing complex geometries, which are difficult to produce by conventional technologies, can be designed and produced.